Maternal and infant bonding: Concept Paper - Kufakunesu, Lilian; Kasu, Christine Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Maternal-infant bonding is a maternal-driven process that occurs primarily throughout the firstyear of a baby’s life, but may continue throughout a child’s life. It is an affective state of themother; maternal feelings and emotions toward the infant are the primary indicator of maternalinfantbonding. The first hour of life is very critical in any baby’s life and it is the critical hour tocreate a bond between a mother and her baby.Objective: The purpose of the concept analysis was to describe the importance, barriers andconsequences of Maternal-infant bonding. Methods and materialsWalker and Avant model of concept analysis which looks into the attributes, antecedence andconsequences, exemplars and recommendations was used. Literature search was conducted in amonth’s and a half’s time using, bonding journals, Pub- med and MEDLINE, Google and GoogleScholar as search engines. Twenty four studies that were found relevant to the concept of interestwere included in the description of maternal and infant bonding. Maternal and infant bondingwas encouraged in most of the studies.ResultsIt was noted that preconception care plays a vital role in the bonding process as pre conceptionwomen can learn how to bond with their babies even when they are pregnant and not to wait forthe baby to be born.Conclusion and recommendationsMidwives and all other health professionals are encouraged to include maternal and infantbonding in most of the health education sessions.